Additions to the vascular flora of Tunisia - Muller, Serge D. (Hacquetia, 2025)
Over the course of our twenty years of field surveys in Tunisia, we have discovered a number of new taxa in the country that include three alien species (Crassula decumbens, C. helmsii and Euphorbia maculata), one fern (Thelypteris palustris) and eight angiosperms (Alisma lanceolatum, Baldellia repens subsp. repens, Bolboschoenus glaucus, Carex echinata, Crassula vaillantii, Isolepis pseudosetacea, Ononishispida subsp. arborescens, Zannichellia obtusifolia). Sphenopus divaricatus subsp. permicranthus, which was already known on the Tunisian islands, was discovered on mainland Tunisia. Finally, we confirm the presence of Carex panormitana, which was identified from living material for the first time.
Keywords: alien plants; tujerodne rastline; Tunisia; Tunizija